YIELD OF MARGARET QUEEN RADISH HYBRID ACCORDING TO THE SPACING - Santos, Marlei Rosa dos; Moreira, Romário da Silva; Silva, Tadeu Barbosa Martins; Sousa, Ronildo Almeida de; Almeida, Rubenalto da Silva; Carreio, Laércio Gomes (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
Currently, some important hybrids have replaced traditional radish cultivars, without, however, developing necessary studies on the best planting density for different Brazilian conditions. Thus, the present study aimed to evaluate the effect of spacing between rows and plants on the development and yield of the ‘Margaret Queen’ radish hybrid. A randomized blocks experimental design with four replications in a 3 x 3 factorial scheme was used. Three row spacings (10, 15, and 20 cm) and three spacings between plants in the row (3, 6, and 9 cm) were evaluated. The seeds were sown in furrows at 1.0 cm deep, and the harvest was carried out at 28 days after sowing. The following were determined: number of leaves, root diameter, root length, average root weight, non-damaged root yield, damaged root yield, commercial root yield, and non-commercial root yield. The row spacing did not influence the development of the plants, but it affected the root yield. The row spacing of 20 cm had the lowest root yield. The spacings that provided the highest commercial root yield (D>30 mm) of the Margaret Queen radish hybrid were 10 and 15 cm between rows and 6 cm between plants. The 3 cm spacing between plants is the least suitable for the cultivation of the Margaret Queen radish hybrid radish under the studied conditions.